The closing chapter - Denning, Alfred Denning (London : Butterworths, 1983)
This book contains a fascinating account of some leading contentious legal issues of the day, in which he has played a singular part. He discusses the problem of statutory interpretation and explains the legal significance of the new dichotomy between public law and private law as set out in his judgment in o' Reilly v Mackman in 1982.
Includes index.
Includes index. and tables
ocf. 18/10/18
Loans
Keywords: Law; Law reform; Laws - England